Documentation of pressure ulcers in medical records at an internal medicine ward in university hospital in western Sweden - Julia Andersson; Sara Imberg; Kristina Rosengren (Wiley, 2023)
Abstract Objectives Pressure ulcers cause suffering, prolong care periods, and increase mortality. The aim was to describe and analyze the documentation of pressure ulcers and focused on the medical records from an internal medicine ward in a university hospital in western Sweden. Methods A quantitative, retrospective review of medical records was conducted for all care events (n = 1,458) with descriptive statistics. Results Documentation of the pressure ulcers in care plans was 2.1% (n = 31) compared to 6.7 % (n = 46) within final notes written by registered nurses (RN), a lower result compared to PPM (n = 3/14, 21.4%). Risk assessments were carried out in 68 (4.7%) care events, and 31 care plans included pressure ulcers. Moreover, 198 cases of tissue damage were documented, 43 (21.7%) defined as pressure ulcers, the other 147 (74.2%) lacked definition. Conclusions Differences (2.1%-21.4%) highlight improvements; knowledge and communication of pressure ulcers ensure reliable documentation in medical records.